Age-related patterns of ambulatory blood pressure in a large cohort of individuals referred to Italian community pharmacies: results from the templar project. Issue 2 (28th February 2023) - Omboni, Stefano; Ballatore, Tommaso; Rizzi, Franco; Tomassini, Fernanda; Campolo, Luca; Panzeri, Edoardo
Abstract : Objectives: Ambulatory blood pressure monitoring (ABPM) provides extensive information on several BP parameters other than the average BP during daily life. Through this analysis of the TEMPLAR study, we sought to understand better the features of age-related changes in ABP patterns and phenotypes. Methods: ABPMs were obtained in 53 350 individuals visiting 866 Italian community pharmacies (age 3–101 years, 54.3% female individuals). ABPM patterns were assessed across 10-year age categories. Results: SBP steadily increased with age. DBP increased from the youth to the middle adulthood and then declined. Daytime BP was higher than night-time BP, but the difference narrowed with aging, reducing the prevalence of dippers. An enhanced SBP morning surge and increased prevalence of abnormal morning rise were observed with aging. SBP and DBP variabilities increased with age with a typical U or J shape, more evident in the case of DBP. The proportion of participants with ambulatory hypertension increased with age. However, an elevated daytime BP was more common in younger individuals and elevated night-time hypertension in older individuals. The prevalence of white-coat hypertension remained stable or slightly declined through the age groups, whereas that of masked hypertension steadily increased. Conclusion: Our results confirm that ABP patterns interplay and change in a complex way with age. Such changes, particularly the age-related increase in BP variability and prevalence of nocturnal hypertension, nondipping, enhanced morning rise, and masked hypertension, may increase the risk of cardiovascular events and must be carefully considered by the physician when managing BP in the elderly.